Female Caregivers Stress in Caring for Hospitalized Elderly with Chronic Disease at Universitas Sumatera Utara Hospital: A Phenomenology Study - Tumanggor, Roxsana Devi; Elfira, Eqlima; Aizar, Ellyta (Technium Social Sciences Journal, 2021)
The elderly is prone to suffer from physical illness and experience hospitalization due to physiological decline. Researches showed that the majority of the family caregivers are females, who are responsible for the caregiving delivery.This study aims to explore the female caregiver stress caring for hospitalized elderly with chronic illness at USU Hospital, Medan. This research is a qualitative study with a phenomenological approach. The sampling technique was the purposive sampling method with several criteria; female with mild to high stress level, the prominent caregivers in the family, and had been caring the elderly for more than 1 year. The female caregivers would be assessed for stress levels with the Zarit Burden Inventory instrument, which is commonly used to assess the stress burden of caregivers caring for the elderly. The data collection is conducted through in-depth interview. The data are transcribed and analysis for sub-theme and theme. The research result found nine participants with an age range of 32-67 years. All participants are the elderly daughter’s and spouses. The stress score is 15-25 which means that the participants are experiencing mild-moderate to severe stress ranges. The thematic analysis revealed four main themes namely; (1) Financing elderly, (2) Caregiver fatigue, (3) Experiencing negative relationship, and (4) Indonesian culture associated with female gender. According to the research result, it should be a basis data for further research related to the elderly caregivers. Therefore, the need for the specific interventions is provided for the elderly and the caregivers who are vulnerable to stressful conditions.